1974
DOI: 10.1111/j.1476-5381.1974.tb09682.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brain 5‐hydroxytryptamine in the Hyperactivity Produced in Rats by Lithium and Monoamine Oxidase Inhibition

Abstract: Administration to rats of LiCl (3 mEq/kg) subcutaneously twice daily for 3 days followed by monoamine oxidase inhibition with either tranylcypromine (TCP; 20 mg/kg) or pargyline (75 mg/kg) on the fourth day produces a syndrome of hyperactivity indistinguishable from that produced by monoamine oxidase inhibition and l‐tryptophan administration. At least 3 injections of LiCl (3 mEq/kg) are necessary before hyperactivity is seen but one dose of LiCl (10 mEq/kg) 5 h before TCP also caused hyperactivity. The hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 17 publications
4
33
1
Order By: Relevance
“…Central 5-HT function has also been shown to be affected by lithium administration, although its effect on the 5-HT system differs according to the duration of treatment and the brain region studied (Goodwin 1989;Price et al 1990b). Accordingly, it has been shown that acute, but not chronic, lithium administration increases rat brain 5-HT turnover (Grahame-Smith and Green 1974;Minegishi et al 1981;Karoum et al 1986). Acute treatment with lithium potentiates the tranylcypromine-plus l-tryptophaninduced 5-HT syndrome in the rat, a syndrome sensitive to stimulation of 5-HT synthesis (Grahame-Smith and Green 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central 5-HT function has also been shown to be affected by lithium administration, although its effect on the 5-HT system differs according to the duration of treatment and the brain region studied (Goodwin 1989;Price et al 1990b). Accordingly, it has been shown that acute, but not chronic, lithium administration increases rat brain 5-HT turnover (Grahame-Smith and Green 1974;Minegishi et al 1981;Karoum et al 1986). Acute treatment with lithium potentiates the tranylcypromine-plus l-tryptophaninduced 5-HT syndrome in the rat, a syndrome sensitive to stimulation of 5-HT synthesis (Grahame-Smith and Green 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lithium is also a useful augmentation strategy in the treatment of depression (de Montigny et al 1981;Rouillon and Gorwood 1998). Although the underlying neurobiological mechanism remains as yet not fully defined, there is a considerable body of preclinical evidence reporting an increase in 5-HT neurotransmission following lithium administration (Baptista et al 1990;Grahame-Smith and Green 1974;Treiser et al 1981;Blier and de Montigny 1985;Goodwin et al 1986;Goodwin 1989;Price et al 1990b;Sangdee and Franz 1980;Sharp et al 1991).…”
mentioning
confidence: 99%
“…Lithium decreased the spontaneous locomotor activity (1, 2, 3) and the drug-induced hyperactivity in animals (4,5,6,7). On the contrary, lithium, when combined with a monoamine oxidase inhibitor (MAOI), caused hyperactivity in rats (8,9,10), and this hyperactivity syndrome was assumed to be due to an effect of lithium on brain serotonergic and dopaminergic mechanisms.In studies on the pharmacological properties of lithium, we found that the adminis tration of tranylcypromine (TCP), a monoamine oxidase inhibitor, to rats pretreated with LiCI produced a marked and fatal hyperpyrexia in a large proportion of animals. Therefore, we attempted to clarify the possible relationship between the LiCI-'I CP induced hyperpyrexia and brain amines in rats.…”
mentioning
confidence: 99%
“…Lithium decreased the spontaneous locomotor activity (1,2,3) and the drug-induced hyperactivity in animals (4,5,6,7). On the contrary, lithium, when combined with a monoamine oxidase inhibitor (MAOI), caused hyperactivity in rats (8,9,10), and this hyperactivity syndrome was assumed to be due to an effect of lithium on brain serotonergic and dopaminergic mechanisms.…”
mentioning
confidence: 99%
“…However, it should be kept in mind that the measures likely mirror intensity of serotonergic innervations (Schaefer et al, 2008), but not functional activity of neurotransmission. Nevertheless, the range of 5HT content in the homogenized brain is 1 to 2 nmol/g (Baumann et al, 2008a;Bhide et al, 2009;Grahame-Smith et al, 1974;Malberg et al, 1998). Moreover, raphe nuclei have relatively higher contents than other regions (Adell et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%